The Effect Of Environmental Factors On Intertidal Mollusc Assemblages In Penang Island, Malaysia - Abdul Halim, Syazreen Sophia (2017)
Anthropogenic disturbances such as coastal development, land reclamation, artisanal fishing (such as collection of edible mollusc; Donax cuneatus and Meretrix meretrix) and tourism activities have been a threat to intertidal mollusc communities in various aspects. Present study describes the species composition and distribution of molluscs in intertidal region of Penang Island that was influenced by different activities occurring in the area. Five selected sites, i.e. Teluk Aling (TA), Pulau Betong (PB), Jelutong (JT), Teluk Kumbar (TK) and Batu Feringghi (BF) were randomly stratified sampled according to low-, mid-, and high zonation area from May 2015 to January 2016. A total of 30 gastropod and bivalve species belonging to 22 families and 25 genera were identified.